Maternal Deaths due to Obstetric Hemorrhage in Padang, Indonesia: A Case-Control Study: Kematian Maternal Akibat Perdarahan Obstetri di Kota Padang: Sebuah Studi Kasus-Kontrol - Dini F. Omari; Yusrawati; Satya W. Yenny (Indonesian Journal of Obstetrics and Gynecology, 2021)
Abstract Objective: To analyse the association between determinants of maternal deaths and obstetric haemorrhage in Padang, Indonesia.Methods: A retrospective case-control study was conducted in Padang, Indonesia from 2015 to 2019. Maternal deaths that occurred due to obstetric hemorrhage in Padang Health Department was compared to three mothers who survived from obstetric hemorrhage (controls) in Dr. M. Djamil General Hospital, Padang, Indonesia.Results: There were 20 deaths caused by obstetric hemorrhage during 2015 to 2019. Death records could only be found in 16 cases. The most common etiology of obstetric hemorrhage was uterine atony (62.5%). Determinants associated with maternal deaths due to obstetric hemorrhage were interval between pregnancies (p=0.045; OR:10.846), history of previous labour (p=0.003; OR:8.556), and antenatal care (p=0.003; OR:21.364). Age, parity, birth attendant, and mother’s educational level were not significantly associated with maternal deaths due to obstetric hemorrhage.Conclusion: Uterine atony was the most frequent etiology of maternal deaths due to obstetric hemorrhage. There was a significant association between pregnancy intervals, history of previous labour, and antenatal care with maternal deaths due to obstetric hemorrhage.Keywords: determinant, obstetric hemorrhage, maternal death. Abstrak Tujuan: Menganalisis hubungan determinan kematian maternal akibat perdarahan obstetri di Kota Padang.Metode: Sebuah studi retrospektif case-control dilakukan di Kota Padang dari tahun 2015–2019. Setiap kasus kematian ibu akibat perdarahan obstetri dari tahun 2015–2019 yang dilaporkan oleh Dinas Kesehatan Kota Padang dibandingkan dengan tiga kasus perdarahan obstetri yang tidak berakibat kematian di RSUP Dr. M. Djamil Padang. Analisis data menggunakan uji Chi-square.Hasil: Ada 20 kasus kematian akibat perdarahan obstetri selama tahun 2015–2019. Catatan kematian hanya dapat diperoleh pada 16 kasus. Etiologi terbanyak kematian akibat perdarahan obstetri ialah atonia uteri. Determinan yang berhubungan dengan kematian akibat perdarahan obstetri ialah jarak kehamilan (p=0.045; OR:10.846), riwayat persalinan sebelumnya (p=0.003; OR:8.556), dan antenatal care (p=0.003; OR:21.364). Tidak terdapat hubungan yang signifikan antara usia, paritas, penolong persalinan, dan tingkat pendidikan ibu dengan kematian maternal akibat perdarahan obstetri.Kesimpulan: Atonia uteri merupakan etiologi tertinggi kematian maternal akibat perdarahan obstetri. Ada hubungan yang signifikan antara jarak kehamilan, riwayat persalinan sebelumnya, dan antenatal care dengan kematian maternal akibat perdarahan obstetri.Kata kunci: determinan, kematian maternal, perdarahan obstetri.